Labor market trendwatching under wartime conditions: national and regional aspects - Tetiana Miroshnichenko; Dmitro Kozenkov (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article is concerned with the current trends in the development of the labor market in Ukraine under conditions of martial law and military aggression of Russia. It has been established that the changes that have occurred in Ukraine over the past three years have had a significant impact on the economy and employment of the population of the country. The authors have analyzed both qualitative and quantitative parameters of labor force development. In particular, they have identified the trends regarding changes in population structure and size caused by heavy mortality not only by natural causes, but also due to civilian casualties and military casualties on the front line. The influence of migration processes on the changes in the resident population and the unemployment rate in the country has been described. The regional labor market of the Dnipropetrovsk region has been analyzed separately. The disproportions between the demand and supply in the labor market of the Dnipropetrovsk region have been revealed, particularly in terms of the industry-specific orientation of enterprises and types of economic activity. The analysis of nationwide and regional trends in functioning of the labor market shows that there are numerous challenges having significant impact on the staffing support of the economy. The main challenges having impact on the labor market in Ukraine include a nationwide and regional imbalance of the labor force; professional and qualification gap between labor supply and demand; mismatch between professional skills of specialists and the needs of the economy; pressure on the labor market due to the uneven distribution of workers across the country; constant labor outflows and increase in the median age of the workforce; job losses due to the destruction of enterprises or the suspension of their operations.